Summary - Dyson, Ruth (Victoria University of Wellington Law Review, 2003)
This article reflects on the original Woodhouse Report, the blueprint for New Zealand’s current Accident Compensation Scheme. The author argues that the language that the Accident Compensation Corporation (ACC) uses should reflect the principles and substance of the Woodhouse Report rather than the insurance industry. She concludes that the Woodhouse Report should remain fundamental, and ultimately states that New Zealand are fortunate to have the fairness of the visionary scheme.